TRANSPARANSI DAN INTEGRITAS DALAM PENGADAAN ALAT KESEHATAN: PERSPEKTIF ETIKA HUKUM - Ilham Ramadhan Ingo; Mohamad Fajril Pauweni; Nur Fitriyah Rabiasa (Law Journal (LAJOUR), 2026)
The procurement of medical equipment is a strategic sector of public service that is highly susceptible to irregularities, despite being regulated through regulations and electronic procurement systems. Current practices still emphasize procedural transparency and administrative compliance, but do not guarantee the substantive integrity of the procurement apparatus. The research gap in this study lies in the lack of studies that place legal ethics as a normative basis for assessing the legitimacy of medical equipment procurement. This study aims to analyze the application of the principle of transparency in the procurement of medical equipment in hospitals and to emphasize the role of legal ethics in building integrity and preventing irregularities. The research method uses a normative legal approach through legislation and conceptual analysis, with teleological analysis based on deontological ethics theory. The results show that regulation-based and digitalized transparency is not yet effective without the internalization of legal ethics values, thus potentially reducing it to administrative formalities. This study emphasizes the integration of legal ethics as a prerequisite for the legitimacy of procurement, as well as a moral foundation for realizing substantive justice, public interest, and consistent and accountable health governance that is both ethical and sustainable.